2017
DOI: 10.1038/pr.2017.291
|View full text |Cite
|
Sign up to set email alerts
|

5-aza-2′-deoxycytidine, a DNA methylation inhibitor, attenuates hyperoxia-induced lung fibrosis via re-expression of P16 in neonatal rats

Abstract: BackgroundP16 methylation plays an important role in the pathogenesis of hyperoxia-induced lung fibrosis. 5-aza-2'-deoxycytidine (5-aza-CdR) is a major methyltransferase-specific inhibitor. In this study, the effects of 5-aza-CdR on a hyperoxia-induced lung fibrosis in neonatal rats were investigated.MethodsRat pups were exposed to 85% O for 21 days of and received intraperitoneal injections of 5-aza-CdR or normal saline (NS) once every other day. Survival rates and lung coefficients were calculated. Hematoxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Two DNA demethylating agents, 5aza and GA, are capable of normalizing the PPARγ promoter methylation and the fibrotic PPARγ loss, and protecting against pulmonary fibrotic pathologies via their effects on PPARγ (Figure6f). Our data therefore reveal that DNMT aberration and the resultant suppression of PPARγ play causal roles in pulmonary fibrosis, which can be potentially mitigated by modulating DNA methylation.Previous gene-targeting studies of lung tissues or cells of IPF patients have detected altered DNA methylations and expressions of several fibrogenic genes including PTGER2 (prostaglandin E receptor 2), p14 ARF(Cisneros et al, 2012), CDKN2B (cyclin-dependent kinase 4 inhibitor B, p15 INK4b )(Scruggs et al, 2018), p16(Zhao et al, 2017), cyclooxygenase-2 (COX2)(Evans Iona et al, 2016) and Thy-1…”
mentioning
confidence: 99%
“…Two DNA demethylating agents, 5aza and GA, are capable of normalizing the PPARγ promoter methylation and the fibrotic PPARγ loss, and protecting against pulmonary fibrotic pathologies via their effects on PPARγ (Figure6f). Our data therefore reveal that DNMT aberration and the resultant suppression of PPARγ play causal roles in pulmonary fibrosis, which can be potentially mitigated by modulating DNA methylation.Previous gene-targeting studies of lung tissues or cells of IPF patients have detected altered DNA methylations and expressions of several fibrogenic genes including PTGER2 (prostaglandin E receptor 2), p14 ARF(Cisneros et al, 2012), CDKN2B (cyclin-dependent kinase 4 inhibitor B, p15 INK4b )(Scruggs et al, 2018), p16(Zhao et al, 2017), cyclooxygenase-2 (COX2)(Evans Iona et al, 2016) and Thy-1…”
mentioning
confidence: 99%
“…7 ). It has been shown that 5-AzaC treatment reactivates hypermethylated p16 gene promoter [ 74 ]. Nevertheless, more insight into this study will be required to understand the molecular mechanisms behind oxidative or age-related pathogenesis, at least in the eye lens.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, although limited with sample availability and variability, indicates that fibrosis may contribute to both the accelerated progression of PT-NASH. Organ fibrosis is a common debilitating process and previous studies have indicated the efficacy of fibrosis-targeting therapies in other organs ( 33 , 34 ). Given the rapid acceleration of fibrosis in LT recipients diagnosed with PT-NASH, the use of fibrosis-targeting drugs to impede liver fibrosis and attenuate NASH development should be explored.…”
Section: Discussionmentioning
confidence: 99%